Strengthening AYUSH Integration with Preventive Medicine - Vartika Saxena; Puneet Misra; K H Naveen; M M Sumanth; Amity Das; Vama Jain (Indian Journal of Community Medicine)
Integrating Ayurveda, Yoga, Unani, Siddha, and Homoeopathy (AYUSH) into preventive medicine enhances holistic health care by addressing lifestyle, mental well-being, and disease prevention. This integration is vital for addressing India’s quadruple burden of non-communicable diseases (NCDs), communicable diseases, poor maternal and child health (MCH) outcomes, and an aging population. The National Health Policy 2017 promotes this integration through “Pluralism,” aligning with the World Health Organization (WHO)’s Sustainable Development Goal (SDG) 3 and global traditional medicine priorities. Essential actions include adopting integrative care models, standardizing treatment protocols, training healthcare professionals, and advancing research. Despite its promise, challenges persist, such as limited awareness among modern physicians, minimal interaction between practitioners, lack of standardized protocols, and insufficient research on AYUSH’s synergistic effects. The Indian Association of Preventive and Social Medicine (IAPSM) can play a pivotal role in overcoming these barriers. By advocating for policy development, adopting integrative care frameworks, and fostering educational and research collaborations with AYUSH institutes, IAPSM can advance the integration of AYUSH into preventive medicine. Promoting research and increasing public awareness of AYUSH’s role in disease prevention and health promotion is essential for achieving a comprehensive healthcare system.